Anti-anticulturalismo en la antropología filosófica española contemporánea - José Padial, Juan (THÉMATA. Revista de Filosofía, 2012)
Dilthey está en la base de una poderosa corriente heurística en la antropología filosófica española del siglo XX (Ortega, Marías, Zubiri, Polo), cuyos logros permiten a estos autores oponerse al antirelativismo sin tener que recibir la impugnación de culturalismo. The philosophy of Dilthey had a great influence on the Spanish Philosophical Anthropology of XX century, especially in the powerful current of Ortega, Marías, Zubiri and Leonardo Polo. The achievements of these philosophers allow them to oppose racionalism or anti-relativism, without receiving the qualification of culturalism.